TRANSCENDING THE ORDINARY: ARCHETYPAL STRUCTURES IN THE CHILDREN'S FICTION OF SUSAN HILL AND KHUDOYBERDI TUKHTABOYEV - Gulshoda Avloyorova (International Journal of Literature and Language Studies, 2026)
This paper undertakes a comparative archetypal analysis of two children’s novels produced in radically different cultural settings: Susan Hill’s psychological realist narrative “I'm the King of the Castle” and Khudoyberdi Tukhtaboyev’s Uzbek folk-fantasy “Riding Yellow Giant”. Drawing on the archetypal criticism of Jung, Campbell, Frye, and Propp, the study asks whether the deep narrative structures identified in Western mythological criticism — the Shadow, the threshold, the ordeal, the return — organise both texts despite their divergent genres, settings, and outcomes. Close reading of key episodes and character dialogue shows that both novels stage a contest between a vulnerable child-protagonist and a more powerful antagonistic or supernatural figure across a liminal, wooded territory. However, the studies diverge sharply in resolution: Hill’s novel enacts an unredeemed Shadow-encounter ending in the protagonist’s destruction, while Tukhtaboyev’s novel completes Campbell’s full heroic cycle, ending in mastery and return. The paper argues that archetypal criticism illuminates both the cross-cultural persistence of mythic structure in children's literature and the culturally specific ways in which individual literary traditions resolve — or refuse to resolve — the archetypal ordeal.